Uji Efektivitas Ekstrak Daun Sambiloto (A. Paniculata [burm.F] ness) Sebagai Bahan Pengawet Alami Tomat Dan Cabai Merah - Pusung, Widya Astuti; Abram, Paulus Hengky; Gonggo, Siang Tandi (Jurnal Akademika Kimia, 2016)
Preservation synthetically or naturally is intended to extend the storability of tomato and red chili. Sambiloto (A. paniculata [Burm.f] Nees) is containing saponins that has anti-bacterial properties, therefore can be used as a preservative. The aim of this study was to investigate whether the extract of sambiloto leaf can be used as a natural preservative for tomato and red chili, and to determine the concentration of extract of sambiloto leaf which was effectively used as the preservative. The method used in this study was maceration to produce extract and iodometric titration to determine the levels of vitamin C before and after preservation. The results showed that the pickling tomatoes and red chili using extract of sambiloto leaf with a concentration of 6% sustained tomates up to 9 days and red chilies up to 11 days. Level of vitamin C contained in tomatoÂ was decreasing from 39.9 mg/100g to 37.54 mg/100g of material while red chilli is decreasing from 79.78 mg/100g to 72.74 mg/100g of material.